Comparison of Low Field Electron Transport in Zincblende and Wurtzite SiC Structures for High Gain Device Modeling - Hadi Arabshahi (Journal of Applied Computer Science & Mathematics, 2011)
Temperature and doping dependencies of electron mobility in both wurtzite and zincblende SiC structures have been calculated using an iteravive technique. The following scattering mechanisims, i.e, impurity, polar optical phonon, acoustic phonon, piezoelectric and electron plasmon are inculded in the calculation. Ionized imurity scattering has been treated beyound the Born approximation using the phase-shift analysis. It is found that the electron mobility decreases monotonically as the temperature increases from 100 to 500 K. The low temperature value of electron mobilty increases significantly with increasing doping concentration. The iterative results are in fair agreement with other recent calculations obtained using the relaxation-time approximation and experimental methods.